Dry grinding of gears for sustainable automotive transmission production. (1st March 2018) - Guerrini, Giacomo; Landi, Enrico; Peiffer, Klaus; Fortunato, Alessandro
Abstract: Gear production for automotive transmissions is a rapidly growing market as manufacturers adapt to increasingly more stringent automobile fuel-efficiency requirements. Grinding is the preferred choice for finishing of automotive gears thanks to its high productivity and capability of machining heat-treated parts with very high geometric accuracy and surface quality. Grinding remains, however, the only machining process still to use lubricant, with significant costs, health implications and environmental risks. This paper presents a novel technology for grinding of gears without the requirement for oil, while still achieving necessary quality and production targets. The feasibility of this new dry process is assessed by firstly identifying threshold grinding parameters ( 70 m / s cutting speed; 0.4 mm / rev axial feed rate; 82 % and 18 % stock removed via skiving and dry grinding respectively) for avoiding grinding burn, then optimizing cutting parameters to obtain the desired gear accuracy. Gear accuracy and process productivity are found to exhibit opposing dependencies on cutting speed, stock removal and feed rate, with optimization of parameters carried out to achieve current quality and throughput standards. A comparison between results obtained with state-of-the-art wet grinding and the new process confirms the effectiveness and feasibility of dry grinding. Highlights: Automotive transmission gears are ground via novel process performed without lubricants. A threshold grinding energy level is defined, below which grinding burns are avoided. Geometric accuracy of the dry-ground gears is verified. Process parameters are optimized via a DOE technique. Process parameters are realistic for immediate uptake of dry-grinding technology in industrial settings.